Unintegrated Suffering: Healing Disconnections between the Emotional, the Rational, and the Spiritual through Lament. Issue 2 (November 2016) - Rochester, Kathleen M.
Childhood sexual, physical, or emotional abuse can result in splitting many aspects of the emotional and rational sides of a person. Commonly the emotions become confused and difficult to name, and the rational side dominates as a survival mechanism. This can be exacerbated by simplistic teaching that suggests people need to choose to act in certain ways and ignore their emotions. Examples of biblical lament provide helpful models of integration between the rational and emotional sides, encouraging the naming of negative emotions before God, turning to God rather than away from God to an abuser. A realistic grasp of forgiveness and repentance enables wounded people to find healing as they work towards integrating emotions, rationality, and spiritual formation.